The New Covenant at Qumran - Hauw, Andreas (My University, 2018)
This paper answers what the community at Qumran think about new covenant. It covers three manuscripts (Temple Scrolla [11Q19], Rule of the Community [1QS, 4Q255-264a, 5Q11, 5Q13] and Damascus Document [4Q266-273, 5Q12, 6Q15]) because they use the phrase “new covenant” and present notions of the covenant. The proper contexts of the three aforementioned manuscripts, and the only one phrase “new covenant” found in the OT (Jer.31:31), including their theological, political and social issues are discussed. In addition, the emphasis of the concept of covenant in each manuscript and how it relates each other is explained. This paper concludes that the Qumran community reinterpreted the concept of covenant in a new way influenced by theological, political and social issues in its time.
This paper was presented at Society of Asian Biblical Studies (SABS) conference 2018 (16-20 July 2018), STFT Widya Sasana Malang-Indonesia.
Keywords: Covenants -- Religious aspects -- Judaism -- History of doctrines.; Dead Sea scrolls.; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.; Bible -- Criticism, interpretation, etc.